Qualitative analysis of the newly impoverished families in the Republic of Macedonia - Dimitrievska, Vesna (Ревија за социјална политика/Journal of Social Policy, 2015)
The years-long poverty measurements by applying the relative andsubjective method have enabled identification of the basic povertyprofiles.The poverty measurement and observation by the double methodand using the information on the basic structures of state benefits usershave enabled identification of three basic groups of poor families:traditionally poor, newly impoverished families and chronically poorfamilies.The aim of this work is to examine, describe and explain the newlyimpoverished families, using the data obtained from the qualitativemeasurements.It also gives an answer why the qualitative approach was applied inthe measuring of this phenomenon.Newly impoverished families are those that have felt the dynamicdecline of the living standard during the transition period (householdswithout a single employed member, households with employed memberswho do not get salaries on time, households having more members).Various data sources have been used in the analysis: naturalenvironment observation, an interview (individual and group), and varioustypes of written documents. Without any additional interventions of theresearcher, information given by the media were used, conversations ofcitizens and politicians were carefully listened to for this problem. These families had difficulties adjusting to the newly emergedsituation. They mostly try to find a way out of this situation in the greyeconomy. The reproductive situation of the second generation of poorfrom this kind of families is evident.The generalizations made for the researched problem, the newlyimpoverished families, arise mostly from the research elaborated withdetailed information for 20 families (newly impoverished) followedthrough a 10-year period.
Keywords: Poverty; qualitative measurements; qualitative measurements,